Potential Review Assessment with 9 Box Model for Talent Management of State-Owned Company Employee - Rifda Alda Ufaira; Rosatyani Puspita Adiati (TAUJIHAT: Jurnal Bimbingan Konseling Islam, 2025)
The individual potential review assessment is carried out on the basis of a comprehensive evaluation that aims to provide an in-depth picture of the current performance and future potential of an individual employee with the position of Industrial Relations Staff at State-Owned Company X. In addition, through this process, the organization can identify strengths, development areas, and the readiness of employees to take on more strategic roles. Data collection was carried out through several methods, namely psychological measurement, using standardized psychometric test tools to assess cognitive, personality, and behavioural competencies; interviews, to explore employees' motivations, career aspirations, and readiness for new challenges; as well as performance assessment data, as objective comparison material from the results of the evaluation of direct superiors. Based on the results of the analysis, the subjects showed performance that was included in the "High" category, namely consistently achieving targets, having a deep understanding of technical tasks, contributing positively to the team, and having potential in the "High" category, namely having strong analytical skills, adapting to change, and showing a leadership presence that could be further developed. The results of the assessment placed the subject in the "High Potentials" quadrant on the 9 Box Model, indicating that he was one of the potential cadres who should be prepared for higher career paths, especially in the Industrial Relations division. Organizations can use these findings to include subjects in talent pools or candidate lists for succession planning, design development programs, such as job rotation, mentorship, or leadership development programs, and strengthen retention strategies by providing clear career paths and growth opportunities within State-Owned Company X.